The Influence of Study Habits, Digital Literacy, Critical Thinking Skills, Teacher Competence, and the Implementation of Moving Class Learning on the Learning Achievement of 11th Grade Students in Economics Subjects - Rega Oktavia; Desi Areva; Mona Amelia (Global Action and Education for Society, 2026)
This study aims to determine: (1) the effect of study habits on learning achievement, (2) the effect of digital literacy on learning achievement, (3) the effect of critical thinking skills on learning achievement, (4) the effect of teacher competence on learning achievement, (5) the effect of the implementation of moving class learning on learning achievement, and (6) the joint effect of study habits, digital literacy, critical thinking skills, teacher competence, and the implementation of moving class learning on learning achievement. The population of this study consisted of grade XI students of SMA N 1 Lembah Gumanti enrolled in economics learning. The sampling technique used was stratified random sampling, with a total sample of 102 students. Data were collected through questionnaires that had been tested for validity and reliability, as well as student achievement documentation. Data analysis was conducted using multiple linear regression, along with t-tests and F-tests, with the aid of SPSS and Eviews software. The results of the study show that: (1) study habits have a significant effect on economics learning achievement, with a coefficient value of 0.155 and a significance level of 0.000 < 0.05, with stronger effects on students from low-income families; (2) digital literacy significantly affects economics learning achievement, with a coefficient of 0.284 and a significance level of 0.000 < 0.05, with stronger effects on students from high-income families; (3) critical thinking skills show a significant effect, with a coefficient of 0.240 and a significance level of 0.000 < 0.05, being more dominant among students from high-income families; (4) teacher competence also significantly influences economics learning achievement, with a coefficient of 0.240 and a significance level of 0.000 < 0.05, where perceptions of teacher competence have greater effects on students from high-income families; (5) the implementation of moving class learning has a significant effect, with a coefficient of 0.112 and a significance level of 0.036 < 0.05, with stronger effects on students from high-income families; and (6) study habits, digital literacy, critical thinking skills, teacher competence, and the implementation of moving class learning jointly have a significant effect on learning achievement, with an F-value of 9.032 > F-table value of 2.52 and a significance level of 0.000 < 0.05. This indicates that Ha is accepted and H0 is rejected.